Pemberdayaan Perempuan Melalui Pelatihan Manjawet Uwei di Kereng Bangkirai Kota Palangka Raya: Penelitian - Marni Nining; Wahidin; Linggua Sanjaya Usop (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to describe women’s empowerment through Manjawet Uwei training, analyse the inhibiting factors of participation, and identify the benefits and changes in the daily lives of women after attending the training in Kereng Bangkirai, Palangka Raya City. The research employed a qualitative method with data collected through observation, interviews, and documentation. The main informants were housewives who participated in the training and the trainers, while secondary data were obtained from the community and relevant stakeholders. Data analysis followed the model Miles, Huberman, and Saldana, involving data collection, condensation, display, and conclusion drawing. Data validation was conducted using prolonged engagement, triangulation, and member checking as recommended Guba and Lincoln. The findings indicate that women in Kereng Bangkirai have strong motivation to develop Manjawet Uwei skills. The training provided knowledge and ability to process Uwei into economically valuable products such as mats, hats, bags, and wallets. These products have the potential to become tourist souvenirs and sources of additional household income. Beyond economic benefits, the training also supports the preservation of local wisdom from being displaced by mass-produced plastic goods.